Anaesthesia for a Patient with Gorham’s Disease A Very Rare Disease to Report - Nimmi, Nahida Parveen; Alam, Golam Ferdous; Mitra, SP; Aziz, Lutful (Journal of the Bangladesh Society of Anaesthesiologists, 2016)
Gorham disease, which is also known as massive osteolysis, vanishing bone disease or lymphangiomatosis, is an extremely rare condition, characterized by proliferation of vascular channels resulting in destruction and resorption of osseous matrix leading to bone loss, which in turn leads to joint instability and problems during airway management and positioning for surgery. Respiratory involvement may further complicate anaesthesia management. We are reporting the anaesthesia care of a 11-year-old boy of known GS with left sided chylothorax who came for amputation of left arm due to closed injury arm resulting from RTA.He was on cyclical Pamidronate therapy and had completed radiotherapy. JBSA 2016; 29(2): 75-77